OPPORTUNITIES TO INTEGRATE GREEN ECONOMY AND SUSTAINABLE DEVELOPMENT ASPECTS INTO POLICY PLANNING, MONITORING AND EVALUATION PROCESSES IN MONGOLIA - Gonchigsumlaa, Ganzorig (Mongolian Journal of Agricultural Sciences, 2018)
‘Sustainable Development’ becomes core strategic thinking of development agenda in last three decades and recently the ‘Green Economy’ terminology becomes the only tool to achieve it. Both terminologies are not well understood not only among conventional citizens but also among scientists. Sustainable Development is well defined but not the Green Economy. Hence, policy makers face serious challenges to convert the vague concept of Green Economy in the planning processes. The paper investigates the level of knowledge of both terminologies from policy makers and monitoring and evaluation officials of government organizations in Mongolia. A survey was conducted among 267 officials including 157 planners and 110 monitoring and evaluation officials in 2014. The result shows that the most of the planners, and monitoring and evaluation officials view that the ‘Green Economy’ is an environmentally friendly economies. However, important two aspects of the Green Economy misunderstood or never taken into account, which are improving human well-being and social equity. Planners’ understanding of Sustainable Development and Green Economy is better than the monitoring and evaluation officials. The author recommend that to improve the knowledge of the Green Economy and its diverse terminologies among planners and monitoring and evaluation officials.